Supplementation with vitamin D and blood pressure control: evidence-based review - Pinho, Tiago Sá (2022)
Objective: Vitamin D has many cardiovascular pleiotropic effects and its deficit seems to be associated with several cardiovascular diseases. The relationship between vitamin D supplementation and blood pressure values of hypertensive patients is controversial. The purpose of this review is to find evidence for the association between vitamin D supplementation for hypertensive adults and control of their blood pressure values.      Data sources: National Guideline Clearinghouse, National Institute for Health and Care Excellence, Canadian Medical Association Practice Guidelines Infobase, The Cochrane Library, Database of Abstracts of Reviews of Effectiveness, Bandolier, Evidence-Based Medicine Online, and PubMed.     Review method: A search for meta-analyzes (MA), systematic reviews, randomized controlled trials (RCT), and clinical guidelines published between June 2010 and June 2020, in Portuguese and English, was performed using the terms MESH Cholecalciferol, Blood pressure, and Vitamin D. To stratify the level of recommendation was used the Strength of Recommendation Taxonomy, of American Academy of Family Physicians.  Results: One hundred and twenty-three articles were found and two MA and four RCT were selected. MA shows concordant results: there was no evidence of a statistically significant decrease in BP when supplemented with cholecalciferol, however, this was demonstrated when interventions for specific groups were adjusted, such as patients over 50 years old, obesity or high supplementation doses (> 800UI/day). Regarding the RCT, only two of them found relationships with statistical significance, while the remaining two failed to demonstrate a causal correlation. Conclusions: The evidence of the association between cholecalciferol supplementation in hypertensive patients and blood pressure control is unclear. Some studies have been able to demonstrate that in specific populations it seems to act as an adjunct in the treatment of hypertension (SORT C).